Deep-sea biology in undergraduate classrooms: Open access data from remotely operated vehicles provide impactful research experiences - Gerringer, Mackenzie E.; Ismail, Yumna; Cannon, Kayla A.; Camilo Hernández, Arline; Gonzales Peralta, Franchesca; Bohen, Ryan; Cartwright, Joseph C.; Feasley, Austin; Fregosi, Lydia; Lehman, Hannah; Niles, Hailey; Quay, Jillian; et al. (Frontiers in Marine Science, 2023)
Opportunities for students to conduct research in courses increase feelings of belonging in science, retention in STEM majors, and sense of ownership in a student’s educational experience. However, many research fields are challenging to bring to students: for example, deep-sea biology often requires expensive expeditions, restricting participation and accessibility. Access to deep-sea systems has been expanded by programs such as the National Oceanic and Atmospheric Administration's Ocean Exploration (NOAA Ocean Exploration), which uses telepresence to bring deep-sea exploration to a global audience. Here, we present one example of how remotely operated vehicles can engage students in original research. Students in an undergraduate Marine Biology lab at at the State University of New York at Geneseo investigated the relationship between substrate rugosity and biodiversity of cold-water coral communities and associate fauna. The study site in the Pacific Remote Islands Marine National Monument was explored by NOAA Ocean Exploration using NOAA Ship Okeanos Explorer as part of the 2017 Mountains in the Deep Expedition, EX1705. Organism density was greater at higher rugosity levels, suggesting that complex substrates support higher abundances in deep-sea communities. This research experience enhanced student’s understanding of the scientific process, appreciation for deep-sea communities, and engagement in the course. Open access deep-sea data provide impactful opportunities for students to participate in original research, increasing the accessibility and reach of deep-sea science.